Outcome of palmar/plantar digital neurectomy in horses with foot pain evaluated with magnetic resonance imaging: 50 cases (2005–2011). (14th May 2014) - Gutierrez‐Nibeyro, S. D.; Werpy, N. M.; White, N. A.; Mitchell, M. A.; Edwards, R. B.; Mitchell, R. D.; Gold, S. J.; Allen, A. K.
Summary Reasons for performing study There is limited knowledge of the foot lesions that influence the outcome of palmar/plantar digital neurectomy (PDN). Objectives 1) To report the short‐ and long‐term outcomes of horses that underwent PDN to alleviate chronic foot pain due to lesions diagnosed by magnetic resonance imaging (MRI) and 2) factors that may influence the outcome of PDN. Study design Multicentre retrospective study. Methods Medical records of 50 horses subjected to PDN due to chronic foot pain were reviewed. Age, breed, sex, athletic activity, duration of lameness, affected limb(s), response to anaesthesia of the palmar/plantar digital nerves, MRI findings and surgical technique were analysed together with follow‐up data to identify factors that influenced the long‐term outcomes. Results Forty‐six of 50 horses (92%) responded positively to surgery; 40 (80%) were able to return to their previous athletic use for a median time of 20 months (range: 12–72 months). Eighteen (36%) horses developed post operative complications including residual lameness, painful neuromas, or early recurrence of lameness. Horses with pre‐existing core or linear lesions of the deep digital flexor tendon (DDFT) had significantly shorter periods of lameness resolution after surgery than horses with dorsal border lesions of the DDFT or other foot lesions. Conclusions Palmar/plantar digital neurectomy can improve or resolve lameness in horses with foot pain unresponsive to medical therapy without serious post operative complications. However, horses with core or linear lesions of the DDFT should not be subjected to PDN as these horses experience residual lameness or early recurrent lameness after surgery. Magnetic resonance imaging can be used to identify these horses.